Gene effects for maydis leaf blight (Drechslera nutydis) resistance and grain yield in white maize (Zea mays) - DASS, SAIN; ARORA, PAWAN; DHANJU, K S; KUMAR, SURENDER; SINGH, PADAM (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during 1996-98 on the gene effed for muydis leaf blight( Drechslera maydis) disease resistance and grain yield in exotic and indigenous white maize grain (Zea may L.) from line x tester analysis. The experiment was conducted under artificial inoculation conditions. Combining ahility analysis revealed that non-additive genetic variances were more important in the expression of disease resistance and high grain yield. There was no similarity in ranking betwecn per-se performance and its corresponding. sea effects of the crosses. In general,it was found that resistance level of the crosses to maydis leaf blight disease was increased where both the parents were having disease reaction resistant/least susceptible followed by resistant x susceptible irrespective of incidence of male parents. Lines L1, L2, L3 and tester T1 were the best general combiners for disease resistance and high yield. L2 x T1 and L3 x T1 were the most desirable combinations having both high per-se performance and high sea effects tbr the traits under study.